Cartaburro Anna Franceschini - Carlo Mollino, Carlo Mollino - Anna Franceschini - Santandrea, Guido; D'Aurizio, Michele ca. 20./21.Jh; Di Rosa, Vincenzo 1992-; Fabbris, Eva ca. 20./21.Jh; Farronato, Milovan 19XX-; Mourão, João 1975-; Silva, Luís 1978- (Verlag der Buchhandlung Walther und Franz König, 2024)
Cartaburro is a project by Anna Franceschini that stems from the research on a gaze. She delved into an architecture of allusive meanings that make up the imagery of Carlo Mollino. The book stems from Anna Franceschini’s desire to look again at Carlo Mollino’s gaze. She delves into its ambiguities, looking for parallels with her practice: the connections between object and subject, the observed and observer, the staging of bodies and objects and their performativity. The volume follows a research which led the artist to create works showcased between 2018 and 2019 at Almanac’s locations in Turin and London, entered the GAMeC collection in Bergamo
Keywords: Franceschini, Anna -- 1979-; Mollino, Carlo -- 1905-1973; Rezeption; Franceschini, Anna / Exhibitions; Mollino, Carlo / 1905-1973 / Influence / Exhibitions; Video installations (Art) / Exhibitions; Installations vidéo (Art) / Expositions